2005
DOI: 10.1007/s00464-003-2187-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic feeding jejunostomy: A systematic review

Abstract: Laparoscopic feeding jejunostomy is a viable method to obtain enteral access with the advantages of minimally invasive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 37 publications
8
33
1
1
Order By: Relevance
“…Fundoplication (open or laparoscopic) with or without gastrostomy is a good option for children with the ability to swallow, even accepting the risk of failure of the fundoplication. It has been suggested that a feeding jejunostomy (open or laparoscopic) is a less complex procedure [16] and we indeed advocate it for the very high-risk ill children where major surgery carries a far greater risk. However, a feeding jejunostomy, although useful for nutrition, does not stop acid reflux with possible catastrophic consequences.…”
Section: Discussionmentioning
confidence: 94%
“…Fundoplication (open or laparoscopic) with or without gastrostomy is a good option for children with the ability to swallow, even accepting the risk of failure of the fundoplication. It has been suggested that a feeding jejunostomy (open or laparoscopic) is a less complex procedure [16] and we indeed advocate it for the very high-risk ill children where major surgery carries a far greater risk. However, a feeding jejunostomy, although useful for nutrition, does not stop acid reflux with possible catastrophic consequences.…”
Section: Discussionmentioning
confidence: 94%
“…If present, an EGD and dilatation could be performed. Additionally, a feeding jejunostomy for postoperative nutritional support is imperative in the treatment of LSG leaks as described in the literature [6,10,34,35]. Feeding jejunostomy also permits avoidance, the excessive proximal flow that could increase the output of the leak.…”
Section: Discussionmentioning
confidence: 98%
“…Viable technique that has replaced SOG is less invasive laparoscopic approach [75,76]. In patients undergoing laparotomy and who will need long tern gut access for nutrition support SOG or FJ should be done at the time of the operation.…”
Section: Laparoscopic Tube Placementmentioning
confidence: 99%